Impact of Ionic Strength on Colloid Retention in a Porous Media: A Micromodel Study - Nishad, Safna; Al-Raoush, Riyadh I. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Release of deposited colloids in the soil porous media during two-phase flow poses potential health hazard due to the facilitated transport of contaminants towards groundwater reservoirs. Considerable uncertainties exist concerning the impact of ionic strength on pore-scale mechanisms of colloid mobilization during transient flow. This study aims to investigate the effect of ionic strength on colloid retention and mobilization using a glass micromodel. The behavior of Carboxylate modified Polystyrene latex particles of 5 ?m diameter in saline solution (i.e., 100 mM & 1 mM of NaCl at pH 10) was visualized with an optical microscope during saturated and twophase flow. We found that colloid aggregation and attachment on Solid-Water Interfaces (SWI) was increased with increase in ionic strength. CO2 injection into the saturated micromodel mobilized the previously attached colloids on SWI, retained at the Gas- Water Interfaces (GWI) due to capillary forces and thus were transported through the micromodel. Imbibition mobilize colloids from GWI and are transported or reattached on SWI depending on the ionic strength of pore water. The greater adhesive forces of colloids at higher ionic strength was resulted in thin film attachment during drainage and reattachment of colloids mobilized from GWI on SWI during imbibition. The acquired images showed the application of a micromodel for the visualization of colloid retention and re-mobilization through the porous media.